Anwar come back : gelombang reformasi ke dua - Mohd. Sayuti Omar, 1960- (Kuala Lumpur : Tinta Merah, 2004)
Reform of the judiciary in Malaysia regarding the release of Anwar Ibrahim, former Deputy Prime Minister of Malaysia.
In Malay.
Koleksi Sumbangan : Dr. Syed Husin Ali
Cover title.
Keywords: Anwar Ibrahim, -- 1947-; Malaysia -- Politics and government